The same goes for art classes in private schools specific properties - Botirov, Jahongir Sobirovich; Bakaev, Shodijon Shokirovich; Avliyakulov, Muzaffar Muhammedovich; Shirinov, Alisher Latipovich; Abdullaev, Sukhrob Sayfullaevich (The journal of contemporary issues in business and government, 2021)
Fine arts classes are considered to be one of the main subjects in the educational process in special schools. Because art classes serve to enrich children's artistic and aesthetic worldview. Under the influence of fine arts, children's level of emotional knowledge increases, and their mental and volitional qualities develop. Correction of hand motor skills is also effective. It is important to strengthen students' ability to work with plot drawings, to create attractive images, to strengthen the ability to place any image correctly on the surface of the paper, and to develop the ability to draw independently.